The reality of data-driven ecosystems: how do theoretic benefits hold true in practice? - Maarten de Mildt; Sofie Verbrugge; Didier Colle (International Telecommunications Society (ITS), 2023)
The concept of data-driven ecosystems is proposed as a solution to manage increasingly complex data processes. A common narrative is that, using an ecosystem approach, an increased amount of data will be available, of higher quality, and this will lead to an increase in innovation. Even though these benefits seem promising at first, it is not standard practice yet. A critical look at the way the market is implementing this concept was needed. A market analysis was performed, linking ecosystem types to benefits expected in theory, and offered in practice by ecosystem initiator services. Three main ecosystem types, based on their scope, were identified and analysed: 1) singleorganisation ecosystems, 2) application domain specific ecosystems and 3) cross-domain ecosystems. This revealed two main insights. On the one hand, achieving the innovation potential remains a challenge, especially for more broadly scoped ecosystems. On the other hand, the services offered in the more broadly scoped ecosystems, do support this potential. Therefore, providing an answer to the question "how do theoretic benefits hold true in practice?".
Keywords: 330; data-driven ecosystem; data ecosystem; ecosystem initiator; benefit analysis; value offering; market analysis